Diagnosing the diagnostic and statistical manual of mental disorders - Cooper, Rachel Valerie (Karnac, 2014)
"The Diagnostic and Statistical Manual of Mental Disorders, more commonly known as the DSM, is published by the American Psychiatric Association and aims to list and describe all mental disorders. The publication of DSM-V in 2013 brought many changes. Diagnosing the Diagnostic and Statistical Manual of Mental Disorders is written for all those who wonder whether the DSM-V now classifies the right people in the right way. It is aimed at patients, mental health professionals, and academics with an interest in mental health. Issues addressed include: What are the main changes that have been made to the classification? How is the DSM affected by financial links with the pharmaceutical industry? To what extent were patients involved in revising the classification? How are diagnoses added to the DSM? Does medicalisation threaten the idea that anyone is normal? What happens when changes to diagnostic criteria mean that people lose their diagnoses? How important will the DSM be in the future?"--Publisher's description